Superconvergence of Mixed Methods for Optimal Control Problems Governed by Parabolic Equations (Advances in Applied Mathematics and Mechanics, 2011)
In this paper, we investigate the superconvergence results foroptimal control problems governed by parabolic equations withsemi-discrete mixed finite element approximation. We use the lowestorder mixed finite element spaces to discrete the state and costatevariables while use piecewise constant function to discrete thecontrol variable. Superconvergence estimates for both the statevariable and its gradient variable are obtained.